2000
DOI: 10.1038/labinvest.3780017
|View full text |Cite
|
Sign up to set email alerts
|

FK506 Augments Glucocorticoid-Mediated Cyclooxygenase–2 Down-Regulation in Human Rheumatoid Synovial Fibroblasts

Abstract: SUMMARY: Prostaglandins (PG) formed by cyclooxygenase (COX) enzymes are important mediators of inflammation in rheumatoid arthritis. The contribution of the inducible COX-2 to inflammation in the rheumatoid synovium is well documented. We examined the regulation of COX-2 mRNA and protein expression in response to both glucocorticoids (GC) and FK506 using rheumatoid synovial fibroblasts. Combined treatment of FK506 and a low concentration of dexamethasone (DEX) (10 Ϫ9 M) down-regulated synovial COX-2 mRNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
17
4
Order By: Relevance
“…Thus, the abnormal, constitutive activation of NF-B has been associated with a number of chronic inflammatory arthritides (9). Many antiarthritic drugs, including nonsteroidal anti-inflammatory drugs, inhibit the expression of proinflammatory genes, such as iNOS, COX-2, TNF-␣, and IL-1␤, through suppression of the NF-B pathway (27). This evidence suggests that the regulation of NF-B activation may be an attractive target for the prevention or treatment for arthritic diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the abnormal, constitutive activation of NF-B has been associated with a number of chronic inflammatory arthritides (9). Many antiarthritic drugs, including nonsteroidal anti-inflammatory drugs, inhibit the expression of proinflammatory genes, such as iNOS, COX-2, TNF-␣, and IL-1␤, through suppression of the NF-B pathway (27). This evidence suggests that the regulation of NF-B activation may be an attractive target for the prevention or treatment for arthritic diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Basic fibroblast growth factor stimulates VEGF release through p42/p43 mitogenactivated protein (MAP) kinase in osteoblasts and negatively regulates it by p38 MAP kinase [28]. Harada et al [10,11] reported PGE2, which is synthesized by COX-2 [17], increased VEGF mRNA levels in osteoblastic RCT-3 cells and in rat calvaria-derived osteoblast-enriched cells. Migita et al [17] examined the downregulation of COX-2 in response to glucocorticoids in human rheumatoid synovial fibroblasts and concluded glucocorticoids could reduce VEGF levels by downregulating COX-2 with subsequent reduction of PGE2.…”
Section: Discussionmentioning
confidence: 99%
“…Harada et al [10,11] reported PGE2, which is synthesized by COX-2 [17], increased VEGF mRNA levels in osteoblastic RCT-3 cells and in rat calvaria-derived osteoblast-enriched cells. Migita et al [17] examined the downregulation of COX-2 in response to glucocorticoids in human rheumatoid synovial fibroblasts and concluded glucocorticoids could reduce VEGF levels by downregulating COX-2 with subsequent reduction of PGE2. Under pathologic conditions, VEGF is strongly expressed during the time course of fracture healing [21].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, combined treatment with tretinoin should reduce skin atrophy [76,77] , and ointment preparations containing a glucocorticoid plus a vitamin D analogue may improve psoriasis therapy by reducing side effects [78] . Studies in rheumatoid synovial [54] and murine skin fi broblasts [79] also indicate a synergistic effect of tacrolimus and low-dose dexamethasone which may translate into clinical improvement. Due to the still measurable potential for skin atrophy of glucocorticoids and the lower potency and the risk of photocarcinogenesis with tacrolimus and pimecrolimus [80] , a combination therapy that is safe and effective in longterm treatment of severe cases would be welcome.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Moreover, glucocorticoid response is infl uenced by the cross-talk of nuclear receptor signalling pathways, since the liganded GR does not only form a homodimer, but also heterodimers with the other nuclear receptors and can compete with those for co-factors [18] . Also receptor-associated immunophilins may induce a cross-talk with other signalling cascades as to be derived from studies in synovial fibroblasts [54] and the lung adenocarcinoma-derived A549 cell [8] stimulated with dexamethasone and FK506.…”
Section: Modulation Of Responsivenessmentioning
confidence: 99%